1981
DOI: 10.1016/s0006-3495(81)84853-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of basic myelin protein on multilayer membrane formation

Abstract: The myelin membrane is composed of 75-80% lipids and 20-25% proteins. The lipids are organized into regular multilayers, with the protein incorporated in them. The protein fraction has been found to be relatively simple in comparison with that of plasma membranes, in that two types of protein make up 70-85% of the total membrane protein (Boggs and Moscarello, 1978a). The first of these, the basic protein, makes up about 35% of the total protein, whereas the second, the proteolipid, makes up about 50%. The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…2 is one of the principal constituents of the mammalian myelin sheath and plays a structural role in maintaining myelin stability (1)(2)(3)(4)(5)(6). Immune responses to MBP have been implicated in the pathogenesis of multiple sclerosis (MS), the most common autoimmune disease of the central nervous system in North America and Northern Europe (7,8).…”
Section: Myelin Basic Protein (Mbp)mentioning
confidence: 99%
“…2 is one of the principal constituents of the mammalian myelin sheath and plays a structural role in maintaining myelin stability (1)(2)(3)(4)(5)(6). Immune responses to MBP have been implicated in the pathogenesis of multiple sclerosis (MS), the most common autoimmune disease of the central nervous system in North America and Northern Europe (7,8).…”
Section: Myelin Basic Protein (Mbp)mentioning
confidence: 99%
“…Moreover, MBP develops some secondary structure upon binding to lipids or detergents. Also informative are the studies that localize MBP after insertion into lipid multilayers (Mateu et al, 1973;Demel et al, 1973;Verkleij et al, 1974;Smith, 1977Smith, , 1992Brady et al, 1981;Lampe et al, 1983;Sedzik et al, 1984;MacNaughtan et al, 1985;Haas et al, 1998). However, nearly all of these studies use the aqueous form of MBP, which in being separated from myelin lipids, has lost any substantial secondary structure.…”
Section: Lipid-bound Mbp Promotes/stabilizes Formation Of Myelin-likementioning
confidence: 99%
“…Several studies have demonstrated that MBP, which is an extrinsic, water-soluble protein, can interact with specific lipids and detergents to form ordered assemblies (Smith, 1992) including monolayers (Demel et al, 1973;MacNaughtan et al, 1985) and stacks of bilayers (Mateu et al, 1973;Verkleij et al, 1974;Smith, 1977;Brady et al, 1981;Sedzik et al, 1984;MacNaughtan et al, 1985). Three different experimental approaches have been reported.…”
mentioning
confidence: 99%
“…Myelin is electrically insulating the axons, allowing fast, saltatory nerve impulse conduction. The composition [3,4,5,6,7,8] and structure [9,10] of the myelin sheath are well studied. Myelin is a lipid-rich membrane, composed of 75 -80% anionic and neutral lipids and 20 -25% proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…The composition [3,4,5,6,7,8] and structure [9,10] of the myelin sheath are well studied. Myelin is a lipid-rich membrane, composed of 75 -80% anionic and neutral lipids and 20 -25% proteins [8]. A subset of myelin-specific proteins, which interact closely with the membrane, is well known [11], but little is known about their influence on the membrane structure and dynamics.…”
Section: Introductionmentioning
confidence: 99%